Community-based screening for infantile anemia in an Okinawan village, Japan - Hokama, T.; Yogi, C.; Binns, Colin; Lee, Andy (Hindawi Publishing Corporation, 2011)
Infancy is a vulnerable age group for anemia throughout the world. However, community-based screening for infantile anemia is seldom reported. This study determined the prevalence of anemia among infants in an Okinawan village from 2003 to 2008, in relation to secondary prevention of the condition. The prevalence among infants aged 3–5, 6–12 and 16–23 months was 12.3%, 15.8%, and 4.2%, respectively, based on cross-sectional surveys (n = 3070 ), and was 11.0%, 17.2%, and 3.9% according to another retrospective cohort study (n = 511 ). The relatively low prevalence of anemia at early childhood suggested that previous detection and treatment through early and late infantile screening had been successful.